The Use of Estrone-3-Glucuronide and Pregnanediol-3-Glucuronide Excretion Rates to Navigate the Continuum of Ovarian Activity - Blackwell, Leonard F.; Cooke, Delwyn G.; Brown, Simon (Frontiers in Public Health, 2018)
The patterns of a woman’s normal ovarian activity can take many forms from childhood to menopause. These patterns lie on a continuum ranging from no ovarian activity to a fully fertile ovulatory cycle, but among the other defined patterns are cycles with anovulatory ovarian activity, including luteinised unruptured follicles (LUFs), and ovulatory cycles with deficient or short luteal phases. For any woman, these patterns can occur in any order, and one can merge into the next, without an intervening bleed, or be missed entirely. Consequently, it is not yet possible to predict the pattern of a future cycle, but it is possible to use our knowledge of the continuum to interpret the current cycle, which has clear implications for the management of personal fertility. An individual’s position in the continuum can be monitored directly in real time by daily monitoring of ovarian hormone excretion rates, without either calendar-type calculations or reference to population means and standard deviations. The excretion of urinary estrone glucuronide (E1G) gives a direct measure of follicular growth, and the post-ovulatory rise in urinary pregnanediol glucuronide (PdG) following an E1G peak provides good evidence of ovulation. Specific values of the PdG excretion rate can be used to determine whether a cycle is anovulatory with or without a LUF, or is ovulatory and infertile or ovulatory and fertile. These specific values are important signposts for navigating the continuum. For a woman to take advantage of the knowledge of the continuum, the data must be reliable, and their interpretation has to be based on the underlying science and provided in an appropriate form. We discuss the various factors involved in acquiring and providing such information to enable each woman to navigate her own reproductive life.